The changing epidemiology of paediatric childhood asthma and allergy in different regions of the world - Adamko, D. J.; Hildebrand, Kyla J. (Frontiers in Allergy, 2025)
Allergic disorders encompass a variety of conditions including asthma, atopic dermatitis, food allergy, allergic rhinitis, and eosinophilic esophagitis. These atopic disorders are connected via an abnormal host immune response to the environment. A series of longitudinal cross-sectional studies conducted over the past 3 decades have reported on the epidemiological trends that contribute towards the development of pediatric asthma and allergic disease. Infant birth cohort studies assessing the microbiome have offered clues as to the underlying biological mechanisms and basis for allergic disease. Why this abnormal immune response is occurring is the basis of decades of research and the reasons for this chapter. Our understanding of the biology of the immune system has increased exponentially with the advances in genomic testing, providing further opportunity for targeted treatments and more importantly, primary prevention of atopic disease.